PERAN AFESIP (AGIR POUR LES FEMMES EN SITUATION PRECAIRE) DALAM MASALAH EKSPLOITASI PEREMPUAN DI KAMBOJA - Intan Sri Dewi Elisabet Sianturi; Ahmad Jamaan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research focuses on the non-state actors in Cambodia is called AFESIP. AFESIP is a non-state actors, but are categorized in international organizations, whose role is help overcome or reduce the number of cases or international issues which play a role in AFESIP for women’s rights. AFESIP is an independent non-governmental organization, non-profit, expected sources of funds from donors, but has the vision and mission as well as a number of programs undertaken to help address and alleviate the problem of exploitation of women in Cambodia, year in 2004 to 2012. AFESIP in that year began to grow up and be able to show existence with it experience in nationally and internationally with built of AFESIP in Thailand, Laos and Vietnam. Women exploitation in Cambodia is a result of the occupation of France and Khmer Rouge war in 1863-1978. Overall, this research about AFESIP and the programs, and how it can reduces many women’s exploitation in Cambodia, so it can keep the stabilitation of that state and keep the security for women, especially for women’s right. Key Words: AFESIP, NGO, Cambodia,Women’s exploitation